Factors associated with non-retention in HIV care in an era of widespread antiretroviral therapy. (June 2017) - O'Connell, Sarah; O'Rourke, Anna; Sweeney, Eileen; Lynam, Almida; Sadlier, Corinna; Bergin, Colm
In an era of antiretroviral therapy (ART) for all HIV-1-infected patients, our primary aim was to describe prevalence and characteristics of patients disengaged from care at an urban ambulatory HIV clinic. We conducted a nested case–control study. All patients who disengaged from care (defined as being lost to follow-up for at least one year) from 2007 to 2014 inclusive were identified. Cases were matched to controls in a 1:4 ratio. A total of 1250 cases were included; 250/2289 (10.9%) of patients attending our HIV clinic disengaged from 2007 to 2014. One hundred and twenty-six (50.4%) were heterosexual, 81 (32.4%) were men who have sex with men and 40 (16%) were intravenous drug users. On univariate analysis only, patients with heterosexual risk were more likely to disengage from care (50.4% vs. 33.7%, p: <0.001). Those who disengaged were younger, mean age of 39 (p: <0.001). A higher proportion of patients who disengaged from care was not receiving ART and did not have a suppressed HIV-1 viral load (p: <0.001). On multivariable analysis, Irish patients were less likely to disengage from HIV care (odds ratio: 0.567, p: 0.002). Factors associated with non-retention in HIV care have been identified. A semi-structured interview of those patients who re-engaged will take place to further examine reasons for disengagement from care.